Explosion-proof thermal type gas flow sensor structure analysis and sensor module development - Gwan-Hyung Kim; Hea-Sung Jung; In-Ho Jung (Institute of Advanced Engineering and Science, 2019)
The present study studied structure analysis and sensor modules for explosion-proof thermal type flow sensors that can withstand the poor surroundings of vessel engines and power plants and can be installed in gas lines. The structure analysis evaluated the integrity of the structures of the explosion-proof thermal type flow sensors with finite element analysis, and with regard to the operation of the sensor modules, those sensor modules that can detect environments where vibrations occur or where there are flows of high pressure gases or fluids were researched and developed. The explosion-proof thermal type flow sensor module consists of a sensing part, an adjustment part, and an output part, and a noise prevention circuit was added to secure the stability of the measurement signals. The flow sensor developed with the present study is a sensor module capable of measuring flows in domestic gas engines and gas piping and it is presented as a reliable sensor module because it is strong against vibrations and has excellent explosion-proof performance.